Antibiotic exposure and acquisition of antibiotic-resistant gram-negative bacteria among outpatients at a US Veterans Affairs medical center. Issue 1 (12th January 2022) - Akpoji, Ukwen C.; Wilson, Brigid M.; Briggs, Janet M.; Song, Sunah; Bej, Taissa A.; Perez, Federico; Jump, Robin L. P.
Abstract: Objectives: To assess the prevalence of antibiotic-resistant gram-negative bacteria (R-GNB) among patients without recent hospitalization and to examine the influence of outpatient antibiotic exposure on the risk of acquiring R-GNB in this population. Design: 2-year retrospective cohort study. Setting: Regional Veterans Affairs healthcare system. Patients: Outpatients at 13 community-based clinics. Methods: We examined the rate of acquisition of R-GNB within 90 days following an outpatient visit from 2018 to 2019. We used clinical and administrative databases to determine and summarize prescriptions for systemic antibiotics, associated infectious diagnoses, and subsequent R-GNB acquisition among patients without recent hospitalizations. We also calculated the odds ratio of R-GNB acquisition following antibiotic exposure. Results: During the 2-year study period, 7, 215 patients had outpatient visits with microbiological cultures obtained within 90 days. Of these patients, 206 (2.9%) acquired an R-GNB. Among patients receiving antibiotics at the visit, 4.6% acquired a R-GNB compared to 2.7% among patients who did not receive antibiotics, yielding an unadjusted odds ratio of 1.75 (95% confidence interval, 1.18–2.52) for a R-GNB following an outpatient visit with versus without an antibiotic exposure. Regardless of R-GNB occurrence, >50% of antibiotic prescriptions were issued at visits without an infectious disease diagnosis or issued without documentation of an in-person or telehealth clinical encounter. Conclusions: Although the rate of R-GNBs was low (2.9%), the 1.75-fold increased odds of acquiring a R-GNB following an outpatient antibiotic highlights the importance of antimicrobial stewardship efforts in outpatient settings. Specific opportunities include reducing antibiotics prescribed without an infectious diagnosis or a clinical visit.